2016
DOI: 10.1093/ajh/hpw146
|View full text |Cite
|
Sign up to set email alerts
|

Inactive Matrix Gla-Protein and Arterial Stiffness in Type 2 Diabetes Mellitus

Abstract: In our cross-sectional analysis, circulating dp-ucMGP was independently associated with CF-PWV in type 2 diabetes. This suggests that deficient vitamin K-dependent activation of MGP may lead to large artery stiffening and could be targeted with vitamin K supplementation in the patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 29 publications
4
21
0
2
Order By: Relevance
“…In a variety of patients, dp-ucMGP was strongly increased (which is consistent with the increased disease risk of elevated dp-ucMGP in the general population) as reported by Mayer [33][34][35], Ueland [36,37] and others [38][39][40][41][42]. Increasing levels of dp-ucMGP were also found to represent a strong risk for all-cause mortality.…”
Section: Comments On the Draft Efsa Scientific Opinion On Dietary Refsupporting
confidence: 85%
“…In a variety of patients, dp-ucMGP was strongly increased (which is consistent with the increased disease risk of elevated dp-ucMGP in the general population) as reported by Mayer [33][34][35], Ueland [36,37] and others [38][39][40][41][42]. Increasing levels of dp-ucMGP were also found to represent a strong risk for all-cause mortality.…”
Section: Comments On the Draft Efsa Scientific Opinion On Dietary Refsupporting
confidence: 85%
“…Justifiably, the investigators evaluated the validity of their modeling approach by observing that the data in the hypertensive group was well represented by a simpler model (i.e., with fewer parameters; also see Local minima and overfitting). The model complexity/ overfitting consideration was a major aspect of our study that 702012 Heart failure cfPWV Fibulin-1 Laugesen et al 762013 Diabetes cfPWV Fibulin-1 Mayer et al (90) 2016 General population cfPWV MGP Pivin et al (101) 2015 Family population cfPWV MGP Sardana et al (107) 2017 Diabetes cfPWV MGP Thamratnopkoon et al 139 AGE, advanced glycation end product; cfPWV, carotid-femoral pulse wave velocity (PWV); ␤-PWV, PWV calculated from stiffness index ␤; cPWV, carotid PWV; cDC, carotid distensibility coefficient; baPWV, brachial-ankle PWV; COL1A1, collagen type I ␣1; COL4A1, collagen type IV ␣1; COL3A1, collagen type III ␣1. , Level(s) at which a study assessed arterial stiffening.…”
Section: Content Analysis Of Selected Papersmentioning
confidence: 90%
“…Liabeuf et al indicated that higher dp-ucMGP was significantly associated with a higher odds of peripheral arterial calcification score: odds ratio 1.88 (1.14, 3.11) [ 24 ]. Higher plasma dp-ucMGP was consistently associated with higher carotid-femoral pulse wave velocity (cf-PWV) in populations from different countries [ 25 27 ]. In the MESA study, no association between circulating DCP and cardiovascular calcification was observed in healthy participants [ 17 ].…”
Section: Circulating Vitamin K and Cvd-related Outcomesmentioning
confidence: 99%